Evaluation of activation characteristics of a canine platelet concentrate produced by a commercial double centrifugation system - Tey, Nicole; Koenig, Amie; Hodges, Katie; Brainard, Benjamin M. (Frontiers in Veterinary Science, 2024)
In veterinary medicine there is a dearth of products available for platelet transfusion in patients that are severely thrombocytopenic. There have been a multitude of commercial tabletop platelet rich plasma systems created for use in regenerative medicine. These systems could be a potential alternative source of platelet products for use in transfusion medicine. This study evaluated the concentration, activation, and acid-base characteristics of a double centrifugation platelet concentrate produced by a commercial benchtop PRP system. 10 healthy dogs were used in the study. Mean platelet count in the double centrifuged platelet concentrate was 863 ± 352 x 10 3 /µL, with very low white blood cell contamination (median of 0.47 x 10 3 leukocyte/µL (range 0.15 -2.18 x 10 3 /µL)). The double-centrifuged PRP had similar baseline activation characteristics (as determined by P-selectin expression) as a control single centrifuge PRP (0.76% vs. 0.72% unstimulated, 30.5% vs. 34.9% stimulated, P = 0.432). The benchtop platelet rich plasma systems did not cause excessive activation of platelets during PRP production and should be further investigated as a potential source of fresh platelet concentrates for transfusion purposes.